Longitudinal Trends in Severe Dyslipidemia in the Czech Population: The Czech MONICA and Czech Post-MONICA Study - Cífková, Renata; Bruthans, Jan; Wohlfahrt, Peter; Hrubeš Krajčoviechová, Alena; Šulc, Pavel; Jozífová, Marie; Eremiášová, Lenka; Pudil, Jan; Linhart, Aleš; Widimský, Jiří; Filipovský, Jan; Mayer, Otto; et al. (Journal of cardiovascular development and disease, 2023)
Background: Severe hypercholesterolemia is associated with an increase in the risk of developing atherosclerotic cardiovascular disease. The aim of this analysis was to assess longitudinal trends in severe dyslipidemia (defined as total cholesterol > 8 mmol/L or LDL-cholesterol > 5 mmol/L) in a representative population sample of the Czech Republic and to analyze the longitudinal trends in the basic characteristics of individuals with severe dyslipidemia. Methods: Seven independent cross-sectional surveys were organized in the Czech Republic to screen for major cardiovascular risk factors (from 1985 to 2015-2018). A total of 20,443 randomly selected individuals aged 25-64 years were examined. Results: The overall prevalence of severe dyslipidemia was 6.6%, with a significant downward trend from the fifth survey onwards (2000/2001). Over the study period of 30+ years, the individuals with severe dyslipidemia became older, increased in BMI, and did not change their smoking habits. Total cholesterol and non-HDL-cholesterol decreased significantly in both sexes throughout the duration of the study. Conclusions: Despite a significant improvement in lipids in the Czech Republic from 1985, substantially contributing to the decline in cardiovascular mortality, the number of individuals with severe dyslipidemia remained high, and in most cases, they were newly detected during our screening examinations and were thus untreated.
Keywords: LDL cholesterol; familial hypercholesterolemia; cross-sectional survey; HDL cholesterol; prevalence of severe dyslipidemia; population random sample; total cholesterol